Evaluation of the Technical Assistance Provided by the International Monetary Fund. - International Monetary Fund. Independent Evaluation Office (Washington, D.C. : International Monetary Fund, 2005)
Technical assistance is one of the key services provided by the IMF to member countries-particularly lower income countries. It covers a wide set of activities, from technical assistance to support IMF policy advice to longer-term assistance to support countries' institutional development. This evaluation report examines the relevance and effectiveness of IMF technical assistance, and derives recommendations for both IMF management and the Executive Board.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet